Intrauterine fetal death of one of twins, coexisting with hydranencephaly in the surviving co-twin: a case report (2006)
Hydraenencephaly, a relatively rare malformation of the brain, is characterised by absence of the cerebral hemispheres and their replacement by sacs filled with cerebrospinal fluid. It is one of the recognized forms of intracranial malformations associated with intrauterine fetal demise of one of twins in monochrionic twin gestation. This report illustrates the development of hydranencephaly in a surviving twin sequel to intrauterine fetal demise of the cotwin.